Variation of magnetic braking by non-axisymmetric magnetic fields depending on the perturbed field structure in the KSTAR tokamak. (22nd December 2016) - Kim, Kimin; Jeon, Y.M.; Park, J.-K.; Ko, W.H.; In, Y.; Choe, W.; Kim, J.; Lee, S.G.; Yoon, S.W.; Kwak, J.G.; Oh, Y.K.
Abstract: The variation of a magnetic braking profile by non-axisymmetric magnetic fields has been experimentally demonstrated and numerically validated in the KSTAR tokamak. Two types of n = 2 non-resonant magnetic fields were applied by changing the relative phase of non-axisymmetric field coils. One is even parity, of which non-resonant fields deeply penetrate into the plasma core, and the other is odd parity localized at the plasma edge. The even and odd parity produced significantly different perturbed magnetic field structures, and thereby drove global and edge-dominant toroidal rotation damping, respectively. These distinct braking profiles are consistently reproduced by drift-kinetic particle simulations, indicating the possibility of the predictive utilization of non-resonant magnetic fields for rotation profile control.